The Usability Engineering Lifecycle in Developing a Ludic Application about Scorpions for Children - Halker, Natália Satie M.; Brandão, André L.; Gois, João Paulo (Anais do Workshop sobre Engenharia de Software para Desenvolvimento de Jogos (SE4Games); 2025: Anais do I Workshop sobre Engenharia de Software para Desenvolvimento de JogosDO - 10.5753/se4games.2025.14858, 2025)
Introduction: Given the increasing number of scorpion-related accidents, especially involving children, it is essential to develop educational strategies that promote awareness and prevention of such incidents. Objective: In this context, this article presents the practical application of the Usability Engineering Lifecycle in developing an educational ludic application aimed at children aged 5 to 10. The main goal is to create a playful and accessible tool that helps disseminate information about the risks and safety measures related to scorpions. Methodology: The methodology followed the classic stages of the Usability Engineering Lifecycle - Requirements Analysis, Design, Evaluation, and Development - carried out with the collaboration of experts in health, education, and technology, ensuring that the content and interface were appropriate for the target audience. Results: The results indicate that the developed ludic application has significant potential to promote children’s awareness, contributing to the prevention of scorpion accidents. The study also highlights the importance of integrating usability principles from the early stages of development. It emphasizes the relevance of participatory, user-centered approaches in the context of public health solutions.